Research on the Relationship between the Regulation of Macroeconomic Policies and the Employment Rate of Chinese College Students - Chenjiao, Liu; Raju, Valliappan (International Journal of Psychosocial Rehabilitation, 2020)
China is a country with a large population; thus, unemployment issues in the Mainland are a huge concern. As an important part of social labor, college students have become the focus of the workforce, government, universities, and families. Many experts and scholars have carried out various aspects of analysis and research on the employment situation of college graduates from the economic, political, social, educational, or specific operational aspects. This paper hypothesized relationships between three aspects, namely the country's employment system, higher education and government interventions, and the employment rate of college students. A questionnaire survey was conducted through an online questionnaire network. Finally, after analyses conducted through SPSS and SEM-PLS, it is concluded that the national macro policy has a positive relationship with the employment rate of college students through the employment system, higher education, and government interventions. The macroeconomic policy needs to be adjusted to achieve the goal of improving the employment rate of college students.